Complete color mixing guide for acrylics, oils, and watercolors 2,400 color combinations for each - Barber, John 1932- (Guilford, Connecticut Stackpole Books, an imprint of Global Pequot, 2022)
"With just 25 common paint colors, you can make 2,400 different hues, and they are all illustrated in this comprehensive guide. Better yet, each color mix uses only two paint colors, so matching results are easy to obtain"--Provided by publisher.
"First published by Axis Publishing Limited in 2010"--Colophon.
Includes index.
Keywords: Painting -- Technique; Color guides; Color in art